Hypoxia signals for more muscle cells - Podrabsky, J. E. (The Journal of Experimental Biology, 2010)
Adult phenotypes are the result of both genetic and environmental factors acting to program the form and function of embryonic tissues during development. Skeletal muscle development is known to be plastic for many vertebrate species and is affected by a variety of environmental factors such as temperature and hypoxia. The development of skeletal muscle tissue can be broadly divided into two phases, progenitor cell (myoblast) proliferation which increases the number of developing muscle cells and terminal differentiation which is marked by the expression of a definitive muscle cell phenotype. Both of these events are regulated by insulin-like growth factor (IGF) signaling through the same cellular receptor. Despite using the same receptor, cell proliferation and differentiation are mutually exclusive events in the development of a myoblast. Ren and colleagues at the University of Michigan set out to identify how the same signaling receptor can regulate these two processes and how environmental hypoxia might alter the outcome of IGF signaling in developing muscle cells.